2014
DOI: 10.1371/journal.pone.0110674
|View full text |Cite
|
Sign up to set email alerts
|

LOC401317, a p53-Regulated Long Non-Coding RNA, Inhibits Cell Proliferation and Induces Apoptosis in the Nasopharyngeal Carcinoma Cell Line HNE2

Abstract: Recent studies have revealed that long non-coding RNAs participate in all steps of cancer initiation and progression by regulating protein-coding genes at the epigenetic, transcriptional, and post-transcriptional levels. Long non-coding RNAs are in turn regulated by other genes, forming a complex regulatory network. The regulation networks between the p53 tumor suppressor and these RNAs in nasopharyngeal carcinoma remains unclear. The aims of this study were to investigate the regulatory roles of the TP53 gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 100 publications
(78 citation statements)
references
References 49 publications
1
75
0
1
Order By: Relevance
“…For example, an antisense lncRNA transcribed from the p15 tumor suppressor locus induces alterations to local heterochromatin and DNA methylation status, thereby regulating p15 expression, and may be associated with leukemia oncogenesis (29). TP53-regulated lncRNA (LOC401317) is directly regulated by p53 and has been demonstrated to exhibit antitumor effects in nasopharyngeal carcinoma cells (30). LOC401317 may inhibit cell cycle progression by upregulating p21, and decreasing cyclin D1 and cyclin E1 expression; it may also promote apoptosis through the induction of poly (ADP-ribose) polymerase (PARP) and caspase-3 cleavage (30).…”
Section: Discussionmentioning
confidence: 99%
“…For example, an antisense lncRNA transcribed from the p15 tumor suppressor locus induces alterations to local heterochromatin and DNA methylation status, thereby regulating p15 expression, and may be associated with leukemia oncogenesis (29). TP53-regulated lncRNA (LOC401317) is directly regulated by p53 and has been demonstrated to exhibit antitumor effects in nasopharyngeal carcinoma cells (30). LOC401317 may inhibit cell cycle progression by upregulating p21, and decreasing cyclin D1 and cyclin E1 expression; it may also promote apoptosis through the induction of poly (ADP-ribose) polymerase (PARP) and caspase-3 cleavage (30).…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs compose a large set of RNA molecules that exceed 200 nt in length, completely lack or possess limited protein-coding capacity, and represent a substantial portion of the transcriptome [65][66][67][68][69][70][71][72]. LncRNAs widely regulate gene expression at the epigenetic, transcriptional, and post-transcriptional levels.…”
Section: Discussionmentioning
confidence: 99%
“…LOC401317 was highly induced by p53 transgene expression. Investigating its function in vitro and in vivo as a candidate tumor suppressor showed that LOC401317 was directly transcribed by p53 through a p53-binding site adjacent to its potential promoter region, and that LOC401317 inhibited cell cycle progression by increasing p21 and decreasing cyclin D1/E1 expressions, and promoted apoptosis through the induction of poly(ADP-ribose) polymerase and caspase-3 cleavage [60]. Nevertheless, current available information regarding this and other tumor suppressor lncRNAs involving in pathogenesis of NPC is limited, thus the true roles and functions of these lncRNAs in NPC still remains to be determined.…”
Section: Tumor Suppressor Lncrnasmentioning
confidence: 99%